Sea Level Rise : A Slow Tsunami on America's Shores - Pilkey, Orrin H., 1934-; Pilkey, Keith C., 1965- (Book collections on Project MUSE., 2019)
The consequences of twenty-first-century sea level rise on the United States and its nearly 90,000 miles of shoreline will be immense: Miami and New Orleans will disappear; many nuclear and other power plants, hundreds of wastewater plants and toxic waste sites, and oil production facilities will be at risk; port infrastructures will need to be raised; and over ten million Americans fleeing rising seas will become climate refugees. In this book, the authors argue that the only feasible response along much of the U.S. shoreline is an immediate and managed retreat. Among many topics, they examine sea level rise's effects on coastal ecosystems, health, and native Alaskan coastal communities. They also provide guidelines for those living on the coasts or planning on moving to or away from them, as well as the steps local governments should take to prepare for this unstoppable, impending catastrophe.